Lietuvių draudžiamosios spaudos ir tautinės tapatybės sąsajos - Merkys, Vytautas (Knygotyra, 2005)
It is usually written that the ban of Lithuanian press in Latin and Gothic script in 1864–1904 meant the ban of all Lithuanian press. The reason for this is that Lithuanian press in Cyrillic script was monopolized by Russian authorities and focused on the disintegration and assimilation of the Lithuanian nation. As the comparatively literate Lithuanian nation was boycotting these publications, the banned press grew and became more numerous and richer. The publishing was concentrated in Lithuanian Minor (Prussia, Germany) and the USA and secretly disseminated among Lithuanians in the Russian Empire. This press (books and periodicals) was a major factor in Lithuanian national identity. The distribution of the press was not equal; it depended on the cultural level and national consciousness of the inhabitants. In the part of Lithuania which was actively Polonized (Vilnius episcopate), religious literature played a strong role in the development of Lithuanian national identity. The article investigates the problem of national integration of both parts of the nation (in Russia and in Germany) in the light of the ban on Lithuanian press.